(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Breast cancer is one of the most common malignancies among women worldwide. Surgical treatment often involves partial or complete mastectomy, which can have significant psychological and aesthetic impacts on patients. Reconstructive and plastic surgery plays a crucial role in restoring the breast’s appearance and improving patients’ quality of life. This article explores modern approaches, techniques, and outcomes of reconstructive procedures following breast cancer surgery.